Building Healthy Digital Literacy: Efforts to Mitigate Negative Content at MAN 1 Mataram - Miskal Alfariji; Najwa Falah Yuniawati; Muammal Hamidi; Zidan Ihlasul Amal; Melati Aulia Pertiwi; Amelia Yunia Solehati (al-Afkar, Journal For Islamic Studies, 2026)
This research aims to describe the level of digital literacy among students at MAN 1 Mataram, identify the types of negative content they access, analyze the factors that influence it, and develop an effective digital literacy learning model. This research is motivated by the low level of digital literacy among students, making them vulnerable to negative content in the digital world. The field study was conducted at MAN 1 Mataram, a school with easy internet access and diverse levels of digital literacy. This research uses a qualitative approach with data collection methods through observation, in-depth interviews, and document analysis. Data is analyzed using thematic analysis, data triangulation, and narrative analysis. The results of this research are expected to provide a positive contribution to efforts to build healthy digital literacy at MAN 1 Mataram and provide useful recommendations for other schools in facing similar challenges.